1992
DOI: 10.1111/j.1471-4159.1992.tb08356.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Effects of p‐Chloroamphetamine, d‐Fenfluramine, and Reserpine on Free and Stored 5‐Hydroxytryptamine in Brain and Blood

Abstract: The effects of acute treatment with p-chloramphetamine, d-fenfluramine, and reserpine on intracellular (brain tissue and whole blood) and extracellular (CSF and platelet-free plasma) compartments of 5-hydroxytryptamine (5-HT) in the brain and blood of the same rats have been examined. These treatments affected 5-HT in brain tissue and whole blood similarly (r = 0.823). Reserpine significantly reduced both intracellular pools at 2 and 24 h. p-Chloroamphetamine and d-fenfluramine were more effective on brain tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 38 publications
4
24
1
Order By: Relevance
“…1). These findings differ from those of Martin and Artigas (1992), who did not observe elevations in plasma 5-HT after administration of (ϩ)-fenfluramine (2.5 mg/kg) to rats. The reason for the discrepancy between our results and those of others is not known but could be related to differences in blood sampling procedures.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…1). These findings differ from those of Martin and Artigas (1992), who did not observe elevations in plasma 5-HT after administration of (ϩ)-fenfluramine (2.5 mg/kg) to rats. The reason for the discrepancy between our results and those of others is not known but could be related to differences in blood sampling procedures.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies conducted in the 1990s provide little support for this hypothesis. For example, Martin and Artigas (1992) reported that acute administration of (ϩ)-fenfluramine does not increase plasma 5-HT in rats. Moreover, chronic administration of fenfluramine lowers blood 5-HT in humans (see Rothman et al, 2000b and references therein).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using microdialysis, it was shown that acute reserpine administration increases the extracellular concentration of 5-HT (Martin and Artigas 1992), which could stimulate 5-HT autoreceptors and decrease 5-HT synthesis through a feedback mechanism (Briley and Moret 1993). This is supported by the findings that acute (Tunnicliff et al 1992) or local (Invernizzi et al 1991) administration of buspirone (a 5-HT1A agonist) reduces 5-HT synthesis.…”
Section: C) 14mentioning
confidence: 89%
“…Thirdly, poor metabolisers of fenfluramine derivatives may have a more pronounced exposure to the drug and could be more prone to develop the condition [21]. Lastly, drug-induced alteration of the serotonin pathway might promote the occurrence of PAH [22,23]. By interacting with the serotonin transporter, fenfluramine derivatives release serotonin from platelets and inhibit its reuptake into platelets and pulmonary endothelial cells [22].…”
Section: Discussionmentioning
confidence: 99%